2023
DOI: 10.3390/cells12071099
|View full text |Cite
|
Sign up to set email alerts
|

The αMSH-Dependent PI3K Pathway Supports Energy Metabolism, via Glucose Uptake, in Melanoma Cells

Abstract: Stimulation of melanocytes and murine melanoma cells with αMSH plus the PI3K inhibitor LY294002 resulted in ROS increase, oxidative DNA damage, and pigment retention. We performed cellular and molecular biology assays (Western blot, FACS, immunofluorescence analysis, scratch assay) on murine and human melanoma cells. Treatment with αMSH plus LY294002 altered cortical actin architecture. Given that cytoskeleton integrity requires energy, we next evaluated ATP levels and we observed a drop in ATP after exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Likely because of this signaling bias, the behavior of melanoma cells of identical background but harboring different MC1R forms showed subtle but significant differences in relevant biological properties such as proliferation, cell cycle progression, and response to the genotoxic action of oxidative stress. The functional coupling of the variants to other signaling pathways reported to mediate certain MC1R actions, such as the PPARγ pathway [ 22 , 23 ] or the PI3K pathway [ 22 , 24 , 25 ], has not been investigated, and will be further analyzed in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely because of this signaling bias, the behavior of melanoma cells of identical background but harboring different MC1R forms showed subtle but significant differences in relevant biological properties such as proliferation, cell cycle progression, and response to the genotoxic action of oxidative stress. The functional coupling of the variants to other signaling pathways reported to mediate certain MC1R actions, such as the PPARγ pathway [ 22 , 23 ] or the PI3K pathway [ 22 , 24 , 25 ], has not been investigated, and will be further analyzed in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, work from several laboratories has shown that MC1R signaling is pleiotropic, as it involves not only activation of the cAMP pathway, but also of the peroxisome proliferator activated receptor (PPARγ) pathway [ 22 , 23 ], the PI3K pathway [ 22 , 24 , 25 ], and the extracellular signal regulated protein kinases ERK1 and ERK2 [ 26 ]. ERK1/2 signaling is normally initiated by peptide growth factors binding to receptor tyrosine kinases.…”
Section: Introductionmentioning
confidence: 99%